The 2019 Conference on Artificial Life 2019
DOI: 10.1162/isal_a_00148
|View full text |Cite
|
Sign up to set email alerts
|

Reinforcement Learning Agents acquire Flocking and Symbiotic Behaviour in Simulated Ecosystems

Abstract: In nature, group behaviours such as flocking as well as crossspecies symbiotic partnerships are observed in vastly different forms and circumstances. We hypothesize that such strategies can arise in response to generic predator-prey pressures in a spatial environment with range-limited sensation and action. We evaluate whether these forms of coordination can emerge by independent multi-agent reinforcement learning in simple multiple-species ecosystems. In contrast to prior work, we avoid hand-crafted shaping r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
2

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 21 publications
0
13
0
Order By: Relevance
“…If modeled prey were capable of movement (like fish, deer), active aggregation behaviors such as schooling and flocking could arise. Previous research has shown that flocking can emerge in simple predator-prey systems with limited sensation-action abilities (Sunehag et al, 2019). Our research makes a useful contribution in demonstrating how aggregation can emerge in prey without active aggregating behavior on their part, simply through the impact of evolved search patterns of predators.…”
Section: General Discussion and Future Directionsmentioning
confidence: 72%
“…If modeled prey were capable of movement (like fish, deer), active aggregation behaviors such as schooling and flocking could arise. Previous research has shown that flocking can emerge in simple predator-prey systems with limited sensation-action abilities (Sunehag et al, 2019). Our research makes a useful contribution in demonstrating how aggregation can emerge in prey without active aggregating behavior on their part, simply through the impact of evolved search patterns of predators.…”
Section: General Discussion and Future Directionsmentioning
confidence: 72%
“…For instance, they outperform humans at several video games and strategic board games [9]. There are also many agent-based ecosystem simulators that are based on RL [10,11,12].…”
Section: Models Of Animal Cognitionmentioning
confidence: 99%
“…It is designed to facilitate the implementation of a wide range of locomotion tasks for RL algorithms by introducing self-contained, reusable components which compose into different task variants. The Locomotion framework has enabled a number of research efforts including [9][10][11] and more recently has been employed to support Multi-Agent domains in [12,13] and [14]. Fig.…”
Section: Locomotionmentioning
confidence: 99%